Chkhartishvili-Akunin’s media project: metafictionality as meta-history - Бабай, Павло Миколайович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Of particular relevance to modern literary studies is the study of the media of communicative poetics, which largely offset the traditional modernist paradigms of literary work. A related issue is the study of supertext unity, composed of author’s projects with a complex narrative hierarchy and genre-stylistic hybridity. The typology of literary and medial projects embodying the phenomenon of new historicism in modern Russian literature (the works of V. Sharov, V. Sorokin, E. Vodolazkin, M. Shishkin, etc.) is highlighted. An undoubtedly significant place in this context belongs to the meta-historical project of Boris Akunin. The purpose of this article is to study the literary project of Boris Akunin as a medial system that coordinates the historiosophical motivations of the author with metatextual representations of genre-narrative models characteristic of modern literature. As a methodological key, an analysis of the productive interaction of scientistic and fictitious meanings of the concepts of “history” and “event”, as well as the corresponding cognitive traditions and practices of their understanding, is used. The study showed how “large” historical narratives are demonologized, undergoing the corrective influence of fictional ontological and anthropological models. This makes it relevant to appeal to the genres of jokes and short stories, detective and adventurous versions of a historical novel. The subject-narrative system activates polyphonic means – the interference of speech and the points of view of narrators and actors. Artistic time and space create many variations of the intersection of chronotopes, plot correlations, and motivational roll calls. Thus, the authority of the author is decentralized - he acts as a moderator of a multidiscursive set of telling versions – ‘stories’ and ‘events’. A system of authority masks is created, each of which embodies a new version of the Other’s figure as a carrier of a different creative consciousness, an alternative ideology and a language for describing the world.